Transdermal alcohol monitoring combined with contingency management for driving while impaired offenders: A pilot randomized controlled study. (4th July 2018) - Averill, Farah; Brown, Thomas G.; Robertson, Robyn D.; Tchomgang, Angeline; Berbiche, Djamal; Nadeau, Louise; Ouimet, Marie Claude
ABSTRACT: Objectives : In a pilot randomized controlled trial of contingency management (CM) and transdermal alcohol monitoring (TAM) with offenders driving while impaired by alcohol (DWI), perceptions regarding the acceptability of a TAM device, recruitment issues, and the impact of CM and TAM on alcohol use over a 6-week period were evaluated. The results aimed to inform the design of future trials and programs involving CM and TAM for DWI remediation. Methods : TAM devices were affixed to 37 voluntary, community-recruited male DWI offenders with problem alcohol use. They were randomized to one of 3 groups: (1) CM; (2) alcohol use feedback (FB); and (3) TAM device only (CTL). Quantitative and qualitative data were gathered on the acceptability of TAM devices and recruitment, and alcohol use was monitored via TAM and self-report. Results : The TAM device was perceived positively, with benefits for reducing drinking noted. Nevertheless, some of its inconveniences appeared to influence participant recruitment and attrition, including its large size and limited water resistance. TAM data revealed a significant main effect of time for reduction in weekly peak transdermal alcohol concentration ( P = .02), with a decrease between means of weeks 1 and 6 (M = 0.15, SE = 0.02 vs. M = 0.09, SE = 0.02; P = .005). No significant group effect was detected. Conclusions : TAM is a viable adjunct to CM with DWI offenders, though the TAM device used here may influence both study recruitment and adherence. These findings can guide the design of future studies into CM and TAM for DWI remediation.